Correction: A facile strategy to realize a single/double photon excitation-dependent photosensitizer for imaging-guided phototherapy against HeLa cancer cells at separate irradiation channels. Issue 12 (4th February 2020) - Kong, Lin; Huang, Ze; Zhang, Shuai-Shuai; Song, Jian; Zhang, Yu-Yang; Bai, Xiang-Yang; Yang, Jia-Xiang; Li, Lin
Abstract : Correction for 'A facile strategy to realize a single/double photon excitation-dependent photosensitizer for imaging-guided phototherapy against HeLa cancer cells at separate irradiation channels' by Lin Kong et al., Chem. Commun., 2020, 56, 571–574.